PENGARUH CURRENT RATIO (CR), RETURN ON ASSETS (ROA), EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Noviana Ari Rahayu (Departemen Manajemen, Universitas Syiah Kuala, 2019)
AbstractThis aims for this is to determine the effect of Variable Current Ratio (CR), Return On Assets (ROA), and Earning Per Share (EPS) partially and simultaneously on Stock Prices of manufacturing companies of Automotive and Component sub sectors listed on the Indonesia Stock Exchange in period 2013 -2017. The sample of this study was conducted using a purposive sampling method so obtained 11 companies from 13 companies of the Automotive and Components sub sectors over a period 2013-2017. The data analysis method used is multiple linear regression analysis and hypothesis testing which consists of a partial t test and a F test simultaneously, and test the coefficient of determination (R2). From the data analysis obtained regression equation Harga Saham= 1975,482 - 7,562CR - 17,018ROA + 13,447EPS. Partially Variable Current Ratio (CR) and Earning Per Share (EPS) have a significant effect on Stock Prices, while the Variable Return On Assets (ROA) does not affect the Stock Price. And simultaneously the Variables Current Ratio (CR), Return On Assets (ROA), and Earning Per Share (EPS) have a significant effect on Stock Prices. Analysis of coefficient determination (R2) shows the value of adjusted R square of 88.3%, meaning that the variation in stock prices can be explained by the variables Current Ratio (CR), Return On Assets (ROA), and Earning Per Share (EPS). While the remaining 11.7% is explained by other variables not examined in this study.Keywords Stock Price, Current Ratio (CR), Return On Assets (ROA), and Earning Per Share (EPS)